Автобіографія Федора Ернста початку 1930-х років - Білокінь, С. (Студії мистецтвознавчі, 2009)
During his short lifetime an outstanding Ukrainian art historian Fedir Ernst (1891–1942) wrote a few autobiographies. One of them is the most quoted as it is the most interesting and the most factful. This biography was written between September 19, 1930 and summer, 1931. As the scholar was imprisoned on October 23, 1933 this biography is a review of his activity of the Ukrainian era. Taking into consideration the plots included and avoided this document is suggested to have appeared before his imprisonment and was made for his future reader – his investigator. The autobiography was compared with another document of that period. Preparing himself for being imprisoned Ernst’s chief Andriy Khostyuchenko, a director of Taras Shevchenko All-Ukrainian Historical Museum, made a List of the main workers of All-Ukrainian Historical Museum in Kyiv who were discharged as Trotskyists during 1932 – October, 1934 at the order of Khostyuchenko. Ernst was mentioned in this List as well. Khostyuchenko was discharged on November 5, 1934 and imprisoned on November 3, 1935. The List was kept in his archival and investigative cases. The author focused on mental state of the representatives of the Ukrainian intеllectuals who lived in the totalitarian state and got used to see each other on the opposite sides of the fence till found themselves in the role of future prisoners. So the author told briefly about his actions in the expectation of imprisonment (arrested at the end of April, 1935). Mykhola Zerov copied his poetry, notably sonnets, to give them to his friends for saving. Later, in 1966, his copies were published among The Selected Works. Mykhaylo Orest and Vasyl Chaplenko published many Zerov’s works as well. So we have an addition to autobiography of Fedir Ernst as well as to the biographies of individuals and social history of Kyiv scholar corporation.